2021
DOI: 10.1002/ccd.29890
|View full text |Cite
|
Sign up to set email alerts
|

Stenting as a treatment for cranio‐cervical artery dissection: Improved major adverse cardiovascular event‐free survival

Abstract: Introduction Cranio‐cervical artery dissection (CeAD) is a common cause of cerebrovascular events in young subjects with no clear treatment strategy established. We evaluated the incidence of major adverse cardiovascular events (MACE) in CeAD patients treated with and without stent placement. Methods COMParative effectiveness of treatment options in cervical Artery diSSection (COMPASS) is a single high‐volume center observational, retrospective longitudinal registry that enrolled consecutive CeAD patients over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, fast recognition of CeAD-related clinical symptoms (such as trivial trauma, headaches, or neck pain shortly before the event) and imaging to demonstrate the intramural hematoma, followed by immediate antithrombotic treatment, is vital . Future studies should focus on determining optimal treatment, with regard to both antithrombotic treatment and endovascular therapy with stent placement in a selected group of patients who are at high-risk …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, fast recognition of CeAD-related clinical symptoms (such as trivial trauma, headaches, or neck pain shortly before the event) and imaging to demonstrate the intramural hematoma, followed by immediate antithrombotic treatment, is vital . Future studies should focus on determining optimal treatment, with regard to both antithrombotic treatment and endovascular therapy with stent placement in a selected group of patients who are at high-risk …”
Section: Discussionmentioning
confidence: 99%
“… 25 Future studies should focus on determining optimal treatment, with regard to both antithrombotic treatment and endovascular therapy with stent placement in a selected group of patients who are at high-risk. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single high-volume center study showed that stenting was beneficial to patients, particularly with the development of high-grade stenosis or expanding pseudoaneurysm. [ 20 ] Another study showed that surgical reconstruction could prevent chronic carotid dissection from ischemic or thromboembolic complications if 6 months of anticoagulation treatment failed or progression of dissection occurred. [ 21 ] In patients presenting with symptomatic CAD with acute IS within 4.5 hours of onset, alteplase should be used for intravenous thrombolysis if available and not contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data, therapeutic management of CAD includes the antithrombotic regimen (anticoagulation, signal antiplatelet and dual antiplatelet) [1,[16][17][18] and endovascular intervention (carotid artery stent implantation) [19,20]. The annual recurrent acute stroke rates range from 0.3 to 3.4% and that of transient ischemic attack (TIA) from 0.6 to 1.7% [21].…”
Section: Discussionmentioning
confidence: 99%